COLLABORATIVE PEDAGOGY: TEACHING (WITH) THE GRATEFUL DEAD ON TOUR, ON CAMPUS, AND ONLINE - Adams, Rebecca G. (Dialogue, 9(1,2), 2022)
This essay describes my experiences teaching with the Grateful Dead “on tour” in 1989, on campus in the early 2000s, and online in 2019. Using a life course framework, I discuss how my own development as a teacher, Deadhead, and Grateful Dead scholar and the changing context over time shaped these experiences and how teaching with the Grateful Dead opened a pedagogical space for experimentation that allowed the students and me to take risks and to collaborate despite status differences. Rather than unpacking these experiences entirely, my goal here is to focus on how these three experiences of teaching with the Grateful Dead allowed me to develop and informed my pedagogical approach, particularly my use of technology in teaching. Keywords: Grateful Dead, popular culture, pedagogy, online teaching, technology
Keywords: Type of access: Open Access